Measuring the duration of kangaroo mother care for neonates: a scoping review - Moffat Nyirenda; Cally J Tann; Melissa M Medvedev; Joy Lawn; Eva Loucaides; Victor Spector Tumukunde (BMJ Open)
Objectives Kangaroo mother care (KMC) is high impact for survival of low birth weight neonates, but there are few rigorous evaluations of duration required for impact. We conducted a scoping review of KMC duration measurement methods and assessed their validation.Design Scoping review in accordance with Joanna Briggs Institute guidance for conducting scoping review.Data sources MEDLINE, Embase, Cochrane Library, PsycINFO, African Index Medicus, Latin American and Caribbean Health Sciences Literature, ClinicalTrials.gov, International Clinical Trials Registry Platform, International Standard Randomised Controlled Trial Number Registry, Medrxiv and OpenGrey were searched through November 2022.Eligibility criteria for selecting studies Publications with primary data on KMC duration were included. We excluded short procedural skin-to-skin care studies.Data extraction and synthesis Selection and data abstraction were conducted by two independent reviewers. A data charting form based on the variables of interest was used to abstract data.Results A total of 213 publications were included, of which 54 (25%) documented a method of measuring KMC duration. Only 20 publications (9%) provided a detailed description of the duration measurement method, and none reported validity. Most studies used caregiver reports (29, 54%) or healthcare worker observations (17, 31%). Other methods included independent observers and electronic monitoring devices.Conclusion Only 9% of KMC studies reporting duration documented the measurement method applied, and no studies were found with documented validation of duration measurement methods. Accurate and comparable data on the dose response of KMC will require duration measurement methods to be validated against a gold standard such as an independent observer.